A heuristic approach to the multiple facility location problem - Lapid, Norman Mantaring (2007)
Quantitative heuristic procedures are useful tools for providing solutions to large or intractable problems when conventional optimization approaches cannot be used. Such a heuristic was formulated to provide an alternative method for solving the multiple facility location problem other than the conventional mixed integer linear programming (MILP) approach. The heuristic classifies demand locations according to size, then places and assigns facilities using an iterative series of decision rules designed to balance the competing objectives of improving accessibility and minimizing facility setup cost. In addition, the heuristic model distinguishes between effective and peak capacities and thus allows for the inclusion of penalty costs for exceeding the effective capacity into objective function. The heuristic was implemented using the Java programming language. Six cases of varying size and with different parameters were randomly generated and solved using the heuristic program. The corresponding MILP models were also constructed using the ILOG OPL Development Studio modeling environment and solved with the ILOG CPLEX optimization engine, after which processing times and the generated were compared. It was found that the percentage deviations of the heuristic solutions to the optimal solutions ranged from 5.47% to 21.73%, and the improvement in processing times resulting from the use of the heuristic ranged from 96.9651% to 99.9995%. The conclusion was formed that the heuristic provides a useful alternative for solving the multiple facility problem when the costs or time consumed by using optimization software are prohibitive and that heuristic can be a practical methodology for obtaining solutions to real-life facility location problems.
"May 2007."
Thesis (M.S. Industrial Engineering)--University of the Philippines Diliman.
Keywords: Heuristic programming; Problem solving -- Data processing